PENGUJIAN SIFAT FISIS-MEKANIS DAN NONDESTRUKTIF METODE GELOMBANG SUARA PAPAN WOL SEMEN BERKERAPATAN SEDANG-TINGGI BAMBU BETUNG (DENDROCALAMUS ASPER) - Lina Karlinasari; Dede Hermawan; Akhiruddin Maddu; M. Farouq Iksan; Anita Firmanti (Institut Pertanian Bogor, 2012)
Cement board is a composite wood product has advantages such as fire resistance, termite, water resistant, and has good sound insulation properties. Bamboo is suitable material that can be used as a raw material of cement board. The objectove of this study was to determine the physical-mechanical properties of wool cement boards from betung bamboo (Dendrocalamus asper) in various densities. Mechanical testing included nondestructive testing performed using the sound waves velocity method (stress wave velocity). The material used was particles of wool/ excelsior dimensions. The adhesive used was Portland cement type I by the ratio of bamboo: cement: water 1:2:1. Target board densities were 0.5 g/cm3; 0.8 g/cm3; and 1.0 g/cm3. The results showed the higher density of the board the higher mechanical properties of boards. The difference density cement board was more influential on mechanical properties (MOE, MOR, SW) board compared with those physical properties. Nondestrcutive testing using sound waves velocity method can be used to predict mechanical bending properties of wool cement board of betung bamboo as indicated by the close relationship between the parameter estimators (dynamic MOE) and static testing value (MOE and MOR).